2015
DOI: 10.1016/j.renene.2015.03.043
|View full text |Cite
|
Sign up to set email alerts
|

A new design for natural gas pressure reduction points by employing a turbo expander and a solar heating set

Abstract: a b s t r a c tNatural gas pressure reduction station (CGS) is one of the most important pieces in natural gas transmission system. In a CGS, the high inlet natural gas (NG) pressure has to be reduced down to a much lower value. Pressure reduction is usually implemented by utilizing throttling valves. Due to the positive JouleeThompson coefficient of NG, this pressure drop causes significant temperature fall and consequently hydrate forming in the NG stream. The hydrates may prevent stable NG flow through the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 14 publications
0
20
0
4
Order By: Relevance
“…This task is done by the throttling valve. The heater also warms up the natural gas stream before the pressure reduction process to avoid gas hydrate forming in the natural gas stream [32][33][34].…”
Section: The Current Methods Of Mass Flow Meteringmentioning
confidence: 99%
See 1 more Smart Citation
“…This task is done by the throttling valve. The heater also warms up the natural gas stream before the pressure reduction process to avoid gas hydrate forming in the natural gas stream [32][33][34].…”
Section: The Current Methods Of Mass Flow Meteringmentioning
confidence: 99%
“…This error value in each state could be given by the following equation: For the aim of more professional assessment also, two basic metrics, the MAE (mean absolute error) and STD (standard deviation of absolute error), presented in the following equations, are used to compare and validate the performance of presented correlation [32].…”
Section: The Validation Of Presented Novel Correlationmentioning
confidence: 99%
“…Their numerical simulation results, obtained with the commercial proprietary software Honeywell UniSim Design Suite, showed that an operational costs reduction of about 17% can be achieved with respect to thermal-load-tracking control logic. Arabkoohsar et al [23] also proposed a turboexpander and solar heating set to reduce the heater fuel consumption for a new design of NG letdown stations, and thereby, the net present value analysis method would result in 3.5 years of payback ratio for investment period. Ghaebi et al [24] presented a new combination system for energy harvesting from NG letdown stations.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been accomplished applying solar systems in CGS stations. [6][7][8][9] As an example, Farzaneh-Gord et al 6 studied the feasibility of solar energy for linear heater in the CGS. Their work shows that 100 kWh energy could be saved using this method at the cost of 27,000 USD.…”
Section: Introductionmentioning
confidence: 99%